Tragedy: A very short introduction - Poole, Adrian (Oxford Oxford university press, 2005)
To your local anchorperson, the word "tragedy" brings to mind an accidental fire at a low-income apartment block, the horrors of a natural disaster, or atrocities occurring in distant lands. To a classicist however, the word brings to mind the masterpieces of Sophocles, Shakespeare, and Racine; beautiful dramas featuring romanticized torment. What has tragedy been made to mean by dramatists, storytellers, philosophers, politicians, and journalists over the last two and a half millennia? Why do we still read, re-write, and stage these old plays? This lively and engaging work presents an entirely unique approach which shows the relevance of tragedy to today's world, and extends beyond drama and literature into visual art and everyday experience. Addressing questions about belief, blame, mourning, revenge, pain, and irony, noted scholar Adrian Poole demonstrates the age-old significance of our attempts to make sense of terrible suffering.